2005
DOI: 10.1109/jlt.2005.858232
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of a dynamic code division multiple access communication system based on tunable optical filter

Abstract: Abstract-A dynamic optical code division multiple access (DOCDMA) communication system is proposed for high-bandwidth communication systems. An implementation of the system is proposed based on a fast tunable optical filter (TOF) in each encoder and decoder. This technique actively modulates the central wavelength of a TOF according to a functional code at the transmitter during the bit period before the transmission of the data. The system is modeled and analyzed taking into account multiple access interferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Within the PC family, the WMPC is an improvement over MPC, i.e., double the number of code sequences, higher code weight, and better correlation properties assuming the same PC sequence length [27][28][29][30][31][32][33]. The MPC uses complex analysis methods to increase the code weight to further comply with the auto-correlation peak value.…”
Section: Introductionmentioning
confidence: 99%
“…Within the PC family, the WMPC is an improvement over MPC, i.e., double the number of code sequences, higher code weight, and better correlation properties assuming the same PC sequence length [27][28][29][30][31][32][33]. The MPC uses complex analysis methods to increase the code weight to further comply with the auto-correlation peak value.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of demodulating a specific user signal is complicated, as the other user signals exist in the same bandwidth. 2 In conventional receivers, the presence of other signals is treated as noise. In MUD algorithms, this noise is usually referred to as multiple access interference ͑MAI͒, and it is shown that this type of noise limits direct sequence CDMA ͑DS-CDMA͒ system capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, OCDMA is a popular research area which offers a large bandwidth, more security and low attenuation and can therefore facilitate demanding services such as high-quality video transmission [2]. However, as the data rate on optical fiber increased and transmission lengths increased and the number of wavelengths increased and the optical power levels increased a whole host of nonlinear fiber effects [3].…”
Section: Introductionmentioning
confidence: 99%